Comparison of electrophoretic methods for determination of critical micelle concentration of anionic alkylsulfate surfactants in water/organic environment - Váňová, Jana; Vavříková, Martina; Smetanová, Zuzana; Česla, Petr (Springer, 2019)
The methods for determination of critical micelle concentration of anionic surfactants using capillary electrophoresis instrumentation were compared in this work. We have focused on the determination of critical micelle concentration of homological series of n-alkyl sulfates using four different methods: the electrical current-based method, and method using migration times, retention factors and effective mobilities of n-alkylbenzenes as probe molecules. We have studied the effects of operation conditions (capillary dimensions, applied voltage) and composition of probe samples on the values of critical micelle concentration. The values of critical micelle concentration determined in water and in 25 mmol L−1 borate buffer pH 8.5 without and with addition of 20% (v/v) of acetonitrile ranged from 60 mmol L−1 for sodium nonyl sulfate to 6.1 mmol L−1 for sodium tridecyl sulfate, with higher values for electrolyte containing acetonitrile. The concentration and solvent of probe molecules have significant effect on the determined value of critical micelle concentration. We have studied in detail critical micelle concentration of sodium dodecyl sulfate in mixtures with low concentration of acetonitrile up to the 6% (v/v). In this region, higher uncertainty of determination of critical micelle concentration was experienced.
Porovnání elektroforetických metod pro stanovení kritické micelární koncentrace aniontových tenzidů alkylsíranů sodných ve vodně/organickém prostředí
Keywords: capillary electrophoresis; critical micelle concentration; sodium dodecyl sulfate; acetonitrile; micelles